The Effect of Borax on the Friction Performance of an Automotive Brake Lining - Sugozu, Ilker; Can, Ibrahim; Onerc, Cengiz (Carl Hanser Verlag, 2014)
In this study the effect of refined boron product borax on friction and wear performance of various brake friction couples were investigated. Different amounts of borax were used in the mix with other regular ingredients in the respective brake pad. Newly formulated brake pad material with nine different ingredients was tested using friction assessment and screening test (FAST). Among such specimens, only half of the samples (shown with H indices) were heat treated for 4 h at 180 degrees C. The friction coefficient as well as the wear rate were determined and the friction surfaces were examined by scanning electron microscope (SEM) to assess the performance of these samples. The heat treated sample that was reinforced with 12 % borax exhibited the optimum friction and wear behaviour. With increasing friction surface temperature, a reduction of the friction coefficient of the samples was observed. The lowest reduction of the friction coefficient was observed the 8 % and 12 % borax reinforced and heat treated samples.
Keywords: Materials testing; brake lining; friction; wear